Data-driven static and dynamic resilience assessment of the global liner shipping network. (February 2023) - Bai, Xiwen; Ma, Zhongjun; Zhou, Yaoming
Highlights: A resilience assessment framework for the GLSN across two dimensions, including static resilience and dynamic resilience. Identification of overlapping community structure and key nodes with the clique percolation method. A network disintegration method to consider the impact of traffic flow on system resilience assessment. An innovative, knock-on effect simulation model with tailored, local weighted flow redistribution rules for dynamic resilience assessment. Abstract: As a critical infrastructure system of modern society, the global liner shipping network (GLSN) has become increasingly complex and thus vulnerable to disruptions. This study proposes a resilience assessment framework for the GLSN across two dimensions, including static resilience and dynamic resilience. First, by leveraging high-frequency vessel movement data, the GLSN is constructed. Then, with the clique percolation method (CPM), overlapping community structures and key nodes can be identified. The static resilience assessment is initially conducted using simulation techniques, with nodes attacked through pre-designed scenarios. Then, a network disintegration method is employed to consider the impact of traffic flow on system resilience assessment, which separates the weighted GLSN into different layers for evaluation. The results show that both overlapping community structure and traffic flow significantly impact the resilience evaluation of the GLSN. Finally, to assess the dynamic resilience of the GLSN, we propose an innovative, knock-on effect simulation model with tailored, locally weighted flow redistribution rules. It provides a method for predicting the impacts of potential global disruptions (e.g., the COVID-19 pandemic) and critical maritime infrastructure failures (e.g., the Suez Canal obstruction) on the shipping network, which are of great concern not only to academia but also to industry.